Pennisetum purpureum cv. Cuba CT-115 used as biomass bank. Morphophysiological indicators - Fortes, Dayleni; Herrera, Rafael S.; Cruz, Ana M.; Romero, Aida (Cuban Journal of Agricultural Science, 2016)
This research was carried out with the objective of studying the performance of some morphophysiological indicators after grazing P. purpureum cv. Cuba CT-115 used as biomass bank. A completely randomized sampling was used and a total of 15 tufts were collected (experimental unit) immediately after grazing and every 15 days until to complete each growth cycle. The treatments consisted on the age of the grass regrowth from the moment the animals exit the paddock (zero time) and according to the biomass bank technology. During the first year and for each resting cycle the regrowth age influenced (P<0.001) on the plant height. For more of the cycles the length and width of leaves, and the leaf area increased (P<0.001) with the age and the higher values were in the cycles with more favorable climatic conditions for growth and leaf expansion, reaching the leaf area values of 246 cm2 for the fourth cycle of the first year and 204 cm2 for the fifth cycle of the second year. It was also determined the total yield performance with the regrowth age and growth indexes as Culture Growth Rate (CGR) and Net Assimilation Rate (NAR).The results showed that the growth cycles of the studied crop have an specific response pattern in function of the regrowth age and climatic characteristics. The CGR and the NAR have specific response for each cycle and are appropriate indicators for the analysis and characterization of grass growth. It was also proven that the increase of dry matter yield is done with low efficiency (NAR) from the high Culture Growth Rate is reached. It is recommended to incorporate the growth indexes studied in this research as novel tool for the management of other grasses and forage species.Key words: P. purpureum cv. Cuba CT-115, morphophysiological indicators, biomass bank